2021
DOI: 10.1080/20550324.2021.1917815
|View full text |Cite
|
Sign up to set email alerts
|

On the low reinforcing efficiency of carbon nanotubes in high-performance polymer fibres

Abstract: Driven by the exceptionally high mechanical properties of carbon nanotubes (CNTs), over the years an extensive research effort has been devoted to the reinforcement of high-performance polymer fibres with CNTs. However, to date, improvements in the strength of these fibres have been rather modest even for relatively high CNT contents. After a brief review of CNT reinforced polymer fibres, here, analytical and numerical finite element models will be used to show that these experimental findings are to be expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 106 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…6 Hence, their incorporation into polymers is highly beneficial even at low amounts. 7,8 Moreover, the composite properties are impacted by the level of compatibility between the CNT and the polymer. 9 This might be accomplished by chemical modification of the CNT nano-filler to link specific functional groups, which can better interact with the surrounding macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…6 Hence, their incorporation into polymers is highly beneficial even at low amounts. 7,8 Moreover, the composite properties are impacted by the level of compatibility between the CNT and the polymer. 9 This might be accomplished by chemical modification of the CNT nano-filler to link specific functional groups, which can better interact with the surrounding macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 15 ] used CNTs as nucleating agents of polylactic acid (PLA) to prepare CNTs/PLA composites, and the results showed that the spherulite size of PLA was significantly reduced after the addition of CNTs. However, the high surface energy of CNTs makes it impossible for them to be evenly dispersed in the composite material, and thus the composite materials do not present the expected properties [ 16 ]. Based on the above issues, the current researchers propose that the surface modification of CNTs could solve this problem.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the actual application process, because of the high surface energy of CNTs, agglomeration occurs in the mixing process, which ultimately plays a limited strengthening role or reduces the original properties of the material. 15 basis of the above issues, the current researchers propose that the surface modification of CNTs could solve this problem. 16 At present, the modification of CNTs is mainly focused on a small molecule compound and long chain polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al used CNTs as nucleating agents of polylactic acid (PLA) to prepare CNT/PLA composites, and the results showed that the spherulite size of PLA was significantly reduced after the addition of CNTs. However, in the actual application process, because of the high surface energy of CNTs, agglomeration occurs in the mixing process, which ultimately plays a limited strengthening role or reduces the original properties of the material . On the basis of the above issues, the current researchers propose that the surface modification of CNTs could solve this problem …”
Section: Introductionmentioning
confidence: 99%